Zebrafish tissue injury causes upregulation of interleukin-1 and caspase-dependent amplification of the inflammatory response - Nikolay V. Ogryzko; Emily E. Hoggett; Sara Solaymani-Kohal; Simon Tazzyman; Timothy J. A. Chico; Stephen A. Renshaw; Heather L. Wilson (The Company of Biologists, 2014)
Interleukin-1 (IL-1), the 'gatekeeper' of inflammation, is the apical cytokine in a signalling cascade that drives the early response to injury or infection. Expression, processing and secretion of IL-1 are tightly controlled, and dysregulated IL-1 signalling has been implicated in a number of pathologies ranging from atherosclerosis to complications of infection. Our understanding of these processes comes from in vitro monocytic cell culture models as lines or primary isolates, in which a range and spectra of IL-1 secretion mechanisms have been described. We therefore investigated whether zebrafish embryos provide a suitable in vivo model for studying IL-1-mediated inflammation. Structurally, zebrafish IL-1β shares a β-sheet-rich trefoil structure with its human counterpart. Functionally, leukocyte expression of IL-1β was detectable only following injury, which activated leukocytes throughout zebrafish embryos. Migration of macrophages and neutrophils was attenuated by inhibitors of either caspase-1 or P2X7, which similarly inhibited the activation of NF-κB at the site of injury. Zebrafish offer a new and versatile model to study the IL-1β pathway in inflammatory disease and should offer unique insights into IL-1 biology in vivo.